Redefining the suitable retirement age: comparative and critical analysis from different countries - Nangkula, Utaberta; Alewi, Luqman; Khodabuccus, Muhammad Zeeshan Irfaan; Mohd Yunus, Mohd. Yazid; Ismail, Nor Atiah; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
The paper discuss about the statistics of retirement age in different countries based on developing and developed countries. It defers from different country because of decreasing of death rate and birth rate, evolution of woman social status and many more. In Malaysia, the increasing value of retirement age is due to the decrease of elder population and the increase of trends where woman work for their respective family, Lai Cheng Tung & Jean Dennis Comeau, (2012). This paper will use demographic value to examine the characteristics of differentiation of retirement age in development and developed countries. Developed countries has more successful result of actual retirement age because the government has revised the law concerning stabilization of employment of older person which takes effect, and the mandatory retirement age which increase incrementally the rate of one year of age every three years, until 2025. Mark Schreiber, (2013). There are a lot of theories concerning this topic, suggesting that the procedure and steps for the actual retiring age to appear in government policies and social are really bureaucratic and takes time. By conducting a comparative and critical analysis based on the factors and issues affecting the retirement age and the actual retirement age from different developed and developing countries, such as France, Japan, United Kingdom, India, Mauritius and China we will discuss how the retirement differ from countries and what is the suitable retiring age in general.